If f(a + b) = f(a) + f(b) - 2f(ab) for all nonnegative integers a and b, and f(1) = 1, compute f(1986). ???????

2 Answers
May 24, 2017

f(1986)=0

Explanation:

f(1986)=f(1985+1)=f(1985)+f(1)-2f(1985*1)=1-f(1985)

f(1985)=f(1984+1)=f(1984)+f(1)-2f(1984*1)=1-f(1984)

f(1984)=f(1983+1)=f(1983)+f(1)-2f(1983*1)=1-f(1983)

ldots

f(n)=f((n-1)+1)=f(n-1)+f(1)-2f((n-1)*1)=1-f(n-1)

Now, f(1)=1,f(2)=f(1+1)=f(1)+f(1)-2f(1)=0

Thus, f(1)=1,f(2)=0,f(3)=1,f(4)=0,ldots The function is 1 for odd numbers and 0 for even numbers. Since 1986 is even, f(1986)=0

May 24, 2017

See below.

Explanation:

Considering

f(n+1)=f(n)+f(1)-2f(n)=-f(n)+1

the difference equation

f_(n+1)+f_n=1 has a solution with the structure

f_n = a (1)^n+b(-1)^n so we have

{(f_(n+1)=a+b(-1)^(n+1)+a+b(-1)^n=1),(f_n=a+b(-1)^n = 1):}

solving for a,b we have

a=1/2, b = -1/2(-1)^n so

f_n = 1/2(1-(-1)^n)

so if n is odd

f_(2k+1)=1

and if n is even

f_(2k)=0

so

f(1986)=0